Standard Cold Source Based on Ice Slurry Refrigeration and Uncertainty Analysis - Liang Yongbiao; Xu Geyao; Xie Yuhang; Zhou Long; Zhong Wubin; Li Bincheng; Wu Jianghong (Zhileng xuebao)
The problem of inconsistency between the measurement results of the cooling capacity of room air conditioners between environmental chambers still plagues China's air-conditioning industry and is a meteorological problem that easily leads to conflicts in international trade. A standard cold-source device that can calibrate laboratory measurement results of the enthalpy difference needs to be urgently studied. In this study, a standard cold-source device based on ice slurry refrigeration is proposed, including an ice slurry preparation system and a heat exchange system, based on a study of several mainstream cooling capacity measurement methods for room air conditioners and the research status of standard cold sources at home and abroad, combined with an in-depth understanding of the physical process of ice slurry refrigeration. Experimental research and refrigeration capacity uncertainty analysis are conducted to verify whether the standard cold-source device could calibrate the enthalpy difference laboratory. The experimental results show that the relative uncertainty of the measured cooling capacity of the standard cold-source device in the enthalpy difference chamber can reach 1.2% when setting 0 ℃ on the ambient side and setting the standard cooling condition on the room side with mass flow rate of 70 g/s, which is approximately 1/3 of the air enthalpy method and can be used as a standard cold source to calibrate the cooling capacity measurement results of the enthalpy difference chamber, which can help improve the international competitiveness of the refrigeration industry.